Media Booklet Company Profile CV. Sary Cards Samarinda Penunjang Aktivitas Komunikasi Pemasaran - Sary, Kezia Arum; Wibowo, Sarwo Eddy; Jauhari, Amar Makruf; Ashadi, Arfian Rony (Jurnal Analisis Sosial Politik, 2020)
Sary Cards, located in Samarinda, East Kalimantan, is an industry engaged in the printing and procurement of goods and services. Specific products that are the uniqueness or focus of this printing are in the form of invitations, be it wedding invitations, birthdays, building inaugurations, tasmiyah and so on. However, in today's all-digital era, the printing industry has to undergo many changes with many new competitions through the digital market. Not only changes in the way of selling, but the increasingly diverse products that have begun to shift with technological developments, as well as the way of production. The company profile booklet media is used as a marketing communication activity to be able to survive the competition in this digital era. The compilation of this profile booklet takes a practice-based approach with the communication planning model used is SOSTAC analysis and uses two types of data, primary and secondary.